Deskripsi Saluran Pemasaran Kubis Di Desa Linelean Kecamatan Modoinding Kabupaten Minahasa Selatan - Korompis, Agnes; Waney, Nordy Fritsgerald Lucky; Tarore , Melissa Lady Gisela (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study was to describe the cabbage marketing channel in Linelean Village, Modoinding District, South Minahasa Regency. Data collection was conducted for one month, namely in September 2023, carried out in Linelean Village, Modoinding Subdistrict, South Minahasa Regency and Bersehati Market, Manado City. Data were collected through primary data through the use of questionnaires with interview techniques to respondent farmers, intermediary traders. Secondary data were obtained from the Modoinding sub-district office, BPP office, Linelean village office, Modoinding sub-district. Determination of the research sample using purposive sampling method to determine the sample of farmers who produce cabbage crops in the period January to May 2023, which was obtained as many as 20 farmers, the sample number of traders collectors 2 people, and the sample number of retailers 9 people, and the use of snowball method (snowball sampling) which is determined based on the acquisition of information from the respondent cabbage vegetable farmers where to sell cabbage vegetable crops, and so on to the final consumer level. Data analysis of cabbage marketing channels from the farm level to the final producer using descriptive analysis, as well as the calculation of marketing margins, marketing costs, marketing profits, and farmer's share. The results showed that there were two marketing channels, namely marketing channel-1: farmers to retailers to consumers, and marketing channel-2: farmers to intermediary traders to retailers to consumers. The marketing margin received by each marketing channel, namely marketing channel-1 amounted to Rp1,000 and marketing channel-2 amounted to Rp2,000. Farmer's share is the share received by farmers from the price paid by consumers. Farmer's share of each marketing channel is marketing-1 at 80 percent and channel-2 at 67 percent.